Analysis of digital maturity of the Russian regions - V. V. Stroev; S. V. Sidorenko (Вестник университета, 2024)
The relevance of analysing the digital maturity of regions is due to the country’s desire for transformation in accordance with the concept of the digital economy. The article presents an approach that allows to assess and compare the levels of the digital maturity of various Russian constituent entities. The assessment process uses many indicators, including both infrastructural aspects (availability and quality of the Internet, the development level of telecommunications) and social ones (the degree of population’s digital skills, integration of digital technologies into the educational process and business). The assessment methodology is based on the collection and analysis of statistical data, on surveys of experts and the population as well as on the study of best digitalisation practices at the regional level. The article describes the selection criteria used to classify and rank regions according to their level of the digital maturity. An important part of the research is the analysis of problems that regions face on the way to the digital maturity. The article discusses barriers such as insufficient funding, lack of qualified personnel, underdeveloped infrastructure and low level of digital literacy of the population. Based on this analysis, recommendations are formed to accelerate the process of digitalisation of regions and increase their the digital maturity. The study results offer practical solutions and ways to optimise regional policies that contribute to the improvement of life quality in the regions and ensure the transition to the innovative economic model.